The influence of just in time and total quality management on production cost effieciensy at CV. Daeng Makassar - Widad Ahmad; Ludya Lutfi (Jurnal Mantik, 2023)
This study aims to analyze the effect of Just in Time and Quality Management on Production Cost Efficiency at CV Daeng Kuliner Makassar. The sampling technique in this study was carried out by purposive sampling with the collection technique by distributing questionnaires, namely asking or making a list of questions addressed to respondents in this case to certain employees at CV Daeng Kuliner Makassar which logically relates to the research problem, namely the influence of Just In Time and Total Quality Management on Production Cost Efficiency. The data processing technique in this study uses Smart PLS software. The results of this study indicate that Just In Time partially has a positive and significant effect on Production Cost Efficiency at CV Daeng Kuliner Makassar. Total Quality Management partially has a positive and significant effect on Production Cost Efficiency at CV Daeng Kuliner Makassar. While Just In Time and Total Quality Management simultaneously have a positive and significant effect on Production Cost Efficiency at CV Daeng Kuiner Makassar.